Psychological Inflexibility Moderates Stress and Loneliness in Depression Among Indonesian College Students During the COVID-19 Pandemic - Mega Radyani, Annisa; Hanna Indra, Gracia; Ika Dian Oriza, Imelda (KnE Social Sciences, 2022)
The COVID-19 pandemic has had a tremendous impact on college students’ mental health. Recent studies have found increased perceived stress and loneliness during the pandemic, which are significant risk factors for depression. However, few researchers have specifically discussed the particular factors that can exacerbate the impact of these risk factors on depression. Psychological inflexibility is said to have an important role in facilitating the development of mental health problems. The current study explored the role of psychological inflexibility in moderating perceived stress and loneliness in depression during the COVID-19 pandemic. A cross-sectional study using an online survey was conducted to assess college students’ sociodemographic information, perceived stress, loneliness, and depression during the COVID-19 pandemic. A total of 941 Indonesian college students (age range = 18-39 years old, 74% female) were analyzed using correlation analysis and SPSS macro PROCESS moderation analysis. Several sociodemographic factors such as age, marital status, previous mental health record, education level, perceived impact of COVID-19, income, and financial status were significantly associated with depression and psychological inflexibility, and were thus controlled as covariates. As predicted, higher psychological inflexibility was associated with higher perceived stress, loneliness, and depression. Results showed psychological inflexibility elevated the effect of both perceived stress and loneliness on the depression level. These findings support previous literature regarding the significant role of psychological inflexibility in moderating the development of depression, especially during the COVID-19 pandemic. Based on the findings, it is recommended that alternative interventions are implemented to inhibit the development of depression by decreasing psychological inflexibility, while considering sociodemographic factors. Keywords: OVID-19 pandemic, college student, depression, psychological Inflexibility, perceived stress, loneliness